Towards a Deeper Understanding of Family Influence in the Guidance of Moroccan Muslim Students: Development and Validation of Specific Scales for Successful Guidance - Zemzami, Mountassir; Lotfi, Said (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
In Moroccan Muslim societies, where collectivist and Islamic values shape familial roles, parental practices and family social-financial capital play a pivotal role in students’ career trajectories. However, existing measures rarely capture these intertwined dimensions within this specific socio-cultural framework. This study addresses this gap by conducting two independent studies to develop and validate two scales: the Scale of Parental Practices in Educational and Vocational Guidance (PPEVG) and the Family Social Financial Capital Scope (FSFC). The first study involved 324 Muslim high school students (55% girls) aged 17–18, enrolled in the final year of baccalaureate programs across various academic tracks, from six Moroccan regions, to validate the PPEVG. The second study included 340 Muslim students (62% girls) with the same characteristics to validate the FSFC. Both studies employed multistage cluster sampling. Exploratory (KMO=0.776 and 0.722) and confirmatory factor analyses confirmed the robustness of both scales, with McDonald’s omega coefficients ranging from 0.729 to 0.785. Findings from the PPEVG showed that supportive parental practices (M=16.4) were more prevalent than interfering ones (M=12.9), with a moderate correlation (r=0.36) suggesting that parents may exhibit both behaviors. Parental education significantly influenced practices: higher paternal education correlated with stronger support, while lower maternal education increased interference. FSFC scores highlighted the critical role of socio-financial resources in enabling students' mobility beyond their home region. These findings offer culturally tailored tools for counsellors and actionable insights for policymakers to design inclusive guidance frameworks and address socio-economic disparities in collectivist contexts.